Propagação Vegetativa do Protium spp: Protium heptaphyllum, Protium spruceanum e Protium guacayanum - Lima, Suelen Cristina de Sousa (2012)
The production of secondary metabolites by plant cell culture contributed to the progress in various areas of plant physiology and biochemistry. However, a restricting factor for the definition of protocols to in vitro cell culture oil-producing species such as Protium Heptaphyllum, is contamination of the nutrient medium by microorganisms. This contamination is established in the media and/or in vegetable material, which can be toxic for culture by competing for nutrients, producing toxic substances and inhibiting development of the explant, causing its loss. Thus, , this study aimed to test methods of disinfection for establishment in vitro leaf explants of P. heptaphyllum. Assays were performed at the Laboratory of Tissue Culture Plants at Embrapa Western Amazon, Manaus, Amazonas. For surface disinfection, leaves of P. heptaphyllum, agents were tested in the control of microorganisms: Plant Preservative Mixture (PPM®), Cercobin® with Agrimicina® and essentials oils. It was observed that the PPM® at 1% and 2% was more effective in controlling infection of leaf explants. For the assays with essential oils was obtained control of microbial contaminants, however the concentration used was toxic to the tissue. In view of these results, we suggest new tests with other disinfesting agents, antioxidants for this species. Key words: plant cell culture, in vitro establishment, tropical forest species, micropropagation.